Kartogenin treatment prevented joint degeneration in a rodent model of osteoarthritis: A pilot study. Issue 10 (1st March 2016) - Mohan, Geetha; Magnitsky, Sergey; Melkus, Gerd; Subburaj, Karupppasamy; Kazakia, Galateia; Burghardt, Andrew J.; Dang, Alexis; Lane, Nancy E.; Majumdar, Sharmila
ABSTRACT: Osteoarthritis (OA) is a major degenerative joint disease characterized by progressive loss of articular cartilage, synovitis, subchondral bone changes, and osteophyte formation. Currently there is no treatment for OA except temporary pain relief and end‐stage joint replacement surgery. We performed a pilot study to determine the effect of kartogenin (KGN, a small molecule) on both cartilage and subchondral bone in a rat model of OA using multimodal imaging techniques. OA was induced in rats (OA and KGN treatment group) by anterior cruciate ligament transection (ACLT) surgery in the right knee joint. Sham surgery was performed on the right knee joint of control group rats. KGN group rats received weekly intra‐articular injection of 125 μM KGN 1 week after surgery until week 12. All rats underwent in vivo magnetic resonance imaging (MRI) at 3, 6, and 12 weeks after surgery. Quantitative MR relaxation measures ( T 1ρ and T 2 ) were determined to evaluate changes in articular cartilage. Cartilage and bone turnover markers (COMP and CTX‐I) were determined at baseline, 3, 6, and 12 weeks. Animals were sacrificed at week 12 and the knee joints were removed for micro‐computed tomography (micro‐CT) and histology. KGN treatment significantly lowered the T 1ρ and T 2 relaxation times indicating decreased cartilage degradation. KGN treatment significantly decreased COMP and CTX‐I levels indicating decreased cartilage and bone turnover rate. KGN treatment also prevented subchondral bone changes in the ACLT rat model of OA. Thus, kartogenin is a potential drug to prevent joint deterioration in post‐traumatic OA. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1780–1789, 2016.